Why Do Asset Prices Not Follow Random Walks? - Günter Franke; Erik Lüders (University of Konstanz, Center of Finance and Econometrics (CoFE), 2004)
This paper analyzes the eect of non-constant elasticity of the pricing kernel on asset return characteristics in a rational expectations model. It is shown that declining elasticity of the pricing kernel can lead to predictability of asset returns and high and persistent volatility. Also, declining elasticity helps to motivate technical analysis and to explain stock market crashes. Moreover, based on a general characterization of the pricing kernel, we propose analytical asset price processes which can be tested empirically. The numerical analysis reveals strong deviations from the geometric Brownian motion which are caused by declining elasticity of the pricing kernel.
urn:nbn:de:bsz:352-opus-17565
Keywords: G12; 330; Pricing Kernel; Viable asset price processes; Serial correlation; Heteroskedasticity; Stock market crashes; Kapitalertrag; Börsenkurs; Prognoseverfahren; Wertpapieranalyse; Kapitalmarkttheorie; Risikoaversion; Stochastischer Prozess; Autokorrelation; Theorie